How AI Literacy Drives Digital Entrepreneurial Intention: Evidence from an Emerging Economy - Suchart Tripopsakul; Danupol Hoonsopon (Emerging Science Journal, 2026)
The objective of this study is to examine how artificial intelligence literacy influences digital entrepreneurial intention through cognitive and motivational mechanisms. Drawing on the Theory of Planned Behavior and entrepreneurial cognition, the model incorporates perceived feasibility and perceived opportunity as mediating factors, while self-efficacy and risk-taking propensity are included as moderating variables. Data were collected from 312 adults in Thailand using a structured questionnaire, and the proposed relationships were analyzed using partial least squares structural equation modeling. The results indicate that artificial intelligence literacy has a direct and positive effect on digital entrepreneurial intention and also enhances individuals’ perceptions of feasibility and opportunity. Further analysis confirms that perceived feasibility and perceived opportunity partially mediate the relationship between artificial intelligence literacy and entrepreneurial intention. The moderating analysis shows that self-efficacy strengthens the effect of artificial intelligence literacy on perceived feasibility, while risk-taking propensity has no significant influence on the relationship between artificial intelligence literacy and perceived opportunity. These findings contribute to the understanding of digital entrepreneurship by identifying artificial intelligence literacy as a critical personal capability that stimulates entrepreneurial engagement through both cognitive and motivational pathways, particularly within the context of emerging economies.